Book Review: An Introduction to Sustainable Development by Peter P. Rogers, Kazi F. Jalal and John A. Boyd. (17th May 2010) - Harrison, Jennifer
An Introduction to Sustainable Development, by Peter P. Rogers, Kazi F. Jalal and John A. Boyd. London, UK, Earthscan Publications Ltd., 2008. ISBN: 978-1-84407-520-1